Gender in European forest ownership and management: reflections on women as "New forest owners". Issue 2 (17th February 2017) - Follo, Gro; Lidestav, Gun; Ludvig, Alice; Vilkriste, Lelde; Hujala, Teppo; Karppinen, Heimo; Didolot, François; Mizaraite, Diana
ABSTRACT: The group of female forest owners is growing across Europe and currently estimated to be about 30% of all private owners. This new category of forest owner merits a closer look. By introducing a gender perspective across three different research frameworks, this paper substantiates that gender matters in forest ownership, management, operations, and the understandings of these three aspects. Where gender-disaggregated data is available, and gender is assessed as an empirical variable, we find the differences in numbers between male and female forest owners in most countries. By adding the concept of gender as a relational and structuralizing category, we demonstrate that gender structures affect, for example, actual behavior of female and male forest owners and the self-evaluation of forestry competence. Further, when considering gender as a meaning category we explore how meaning produces behavior and behavior produces meanings, and how both shape institutions and natural and artificial matter. Here forestry competence is the applied example. To further increase the knowledge on new forest owners, we recommend (i) fellow researchers in the field to assume that gender matters and design their empirical studies accordingly and (ii) policy-makers to guarantee access to gender-disaggregated data in official registers and statistics.